Effect of switched-capacitor on super-lift Luo converter - Hussein Abdulkhudhur Hussein; Hassan Jassim Motlak; Harith Nawfal Abdali Almusawi (Institute of Advanced Engineering and Science, 2022)
With the increasing need for solar energy and the need for DC-DC converters that are more efficient, smaller in size, less expensive, and faster in response, in this paper, we will modify the positive output super-lift Luo converter using a switched-capacitor cell. It consists of two capacitors that are charged in parallel and discharged in series to raise the output voltage, the use of capacitors in-stead of inductors increases the voltage, because capacitors are more efficient and have a smaller size than inductors and provide faster and smoother charging and discharging than inductors, so a capacitive cell has been used. The circuit was simulated using the physical security information management (PSIM) program. The current, voltage, and gain co-efficient waves were analyzed and the theoretical equations were proven. The circuit was also linked with the maximum power point tracker using the same program with a solar cell to get the most benefit from the solar energy using this type of converter.